Writing with Rosie : you can write a story too - Giff, Patricia Reilly (Holiday House, 2016)
In a humorous and entertaining guide, two-time Newbery Honor-winning author Patricia Reilly Giff breaks down the process of writing fiction into steps, all while trying to cope with the constant distractions from her exuberant seventy-pound golden retriever puppy, Rosie. Citing examples from her award-winning novels she explains how to proceed with each step in chapter sections titled Can You See What I Did? Young writers can find the inspiration and tips they need to try their hand in sections called Your Turn. Anecdotes from her writing life and hilarious adventures with her high-energy pet provide entertainment and encouragement.